Rural Community-Based Program Strategy of Polisi RW By Sat Binmas in Reducing Aggravated Burglary in Magetan Police Department (Indonesian Journal of Police Studies, 2024)
Burglary with violence is one of the crimes that frequently occurs and draws serious attention from law enforcement authorities in Indonesia. Magetan Regency, as an example, has experienced an increase in burglary cases despite various law enforcement efforts, including the Polisi RW Program initiated by the Chief of the Indonesian National Police (Kapolri). Constraints such as personnel limitations and budgetary constraints are major factors hindering the effectiveness of the program. Additionally, differences in characteristics between urban and rural environments pose unique challenges in the implementation of the Polisi RW program. Therefore, an adaptive and rural community-based strategy is needed to reduce burglary crimes in Magetan Police Resort. This study will examine this strategy with a focus on the role of Sat Binmas in the Polisi RW program. In this study, the researcher employs management theories such as POAC and 6M, interpersonal communication theory, and rural criminology theory along with the concepts of community policing, Sat Binmas, and burglary. A qualitative approach with field research as the research type is utilized. Fact and data collection are conducted through interviews, focus group discussions (FGD), observation, and document examination. Triangulation of sources is used to compare data from different sources. The findings of this study indicate that the implementation of the Community Police (Polisi RW) program in Magetan Regency has adhered to the POAC management strategy as directed by the Central Headquarters of the Indonesian National Police and East Java Regional Police. However, its planning requires adjustment to the current situation in the area to alleviate the workload of the community police. Despite the program's success in fostering interpersonal communication and receiving appreciation from the community, shortcomings persist in addressing more serious criminal issues and surveillance in high-risk areas. Root-level control with the assistance of stakeholders and other relevant parties is necessary to enhance the effectiveness of the Community Police program in Magetan Regency.
Keywords: Strategy; Polisi RW Program; Rural Community; Community Development Unit; Aggravated Bulglary